Managing academic stress among non-formal education students in the digital era: A positive psychology-based systematic scoping review - As, Fatimah; Ningsih, Retno Wahyu; Azni, Fithri (Universitas Jambi, Indonesia, 2026)
This study explores how non-formal education students may manage academic stress in the digital era through a positive psychology perspective. A systematic scoping review was conducted using 13 publications retrieved from Google Scholar, ERIC, PubMed, ProQuest, and JSTOR. The publications were released between 2010 and 2025 and analysed thematically. The selected studies were analyzed thematically. Three main themes emerged: sources of academic stress, positive psychology-based coping resources, and the use of digital tools to support student well-being. The reviewed literature indicates that students may experience stress related to academic workload, professional-identity uncertainty, technostress, information overload, and social comparison. Practices such as gratitude, mindfulness, character-strength development, and supportive relationships may help strengthen resilience and well-being. Digital tools can widen access to these practices. However, institutions should provide support, prioritise privacy, and consider students' access to technology when using these tools.